Trump’s Digital Rhetoric of Hate: The Use of Enthymemes in Creating Division - Tracey J. Hayes (Gonzaga Library Publishing, 2021)
Donald Trump’s divisive rhetoric is a common topic among scholars and citizens of America and the World. Trump’s ability to connect with his followers through Twitter created a different environment than what past politicians encountered due to the unique affordances of social media and the negative attributes of Twitter. Trump’s communication style combined with the rhetorical device of the enthymeme in his tweets conveyed a range of bigoted ideologies, from misogyny to racism to classicism. This paper examines how Donald Trump’s tweets actively promote a hateful divide between Americans by investigating how enthymemes in his tweets are used, the ideographs contained within these enthymemes, the role Twitter’s attributes play, and how rhetor and audience create these understandings together. This analysis explicates the power of Trump’s hateful digital rhetoric and how his continued influence presents a clear and present danger to American democracy.